ANALISIS DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. DUTA PALMA DI KECAMATAN KEMPAS - Sri Astuti; M. Ramli (Indragiri Research Center (ingreat), 2024)
This research aims to determine whether work discipline can influence the work productivity of PT employees. Duta Palma in Kempas District. In this research, the type of data used consists of qualitative and quantitative data, with data collection techniques carried out through interviews and submitting a list of questions (questionnaires). From the research results, it was concluded that there are factors that cause efforts to enforce work discipline to not be able to increase employee work productivity, including enforcement of preventive discipline, corrective discipline and progressive discipline that has not been implemented well or is less strict. As a result of the company's lack of strict enforcement of work discipline, it has not been able to support the increase in work productivity achieved by employees, especially employees in the Palm Oil (CPO) production department. Furthermore, based on quantitative analysis, it shows that simultaneously there is a significant influence between enforcing work discipline through preventive discipline, corrective discipline and progressive discipline on the sub-optimal work productivity of employees in PT's production department. Palma Ambassador. This can be seen from the results of the regression analysis which shows that the adjusted R2 value is 0.917, and this means that 91.7% of work productivity is still less than optimal, influenced by three explanatory variables, namely preventive discipline, corrective discipline and progressive discipline. Meanwhile, the remaining 8.3% is influenced by other variables that are not equalized in the variables of this research.